2022
DOI: 10.1002/jmv.28208
|View full text |Cite
|
Sign up to set email alerts
|

The association between human papillomavirus and bladder cancer: Evidence from meta‐analysis and two‐sample mendelian randomization

Abstract: Introduction Bladder cancer (BCa) is the 10th most common type of cancer worldwide, and human papillomavirus (HPV) is the most common sexually transmitted infection. However, the relationship between HPV infection and the risk of BCa is still controversial and inconclusive. Methods This systematic review and meta‐analysis were conducted following the PRISMA 2020 reporting guideline. This study searched four bibliographic databases with no language limitation. The databases included PubMed (Medline), EMBASE, Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 120 publications
2
27
0
2
Order By: Relevance
“…27,57 A recent meta-analysis has demonstrated that HPV may be involved in the development and progression of BC, as well as contribute to the unfavorable prognosis of patients. 41 Moreover, a study in Iran revealed that HPV positivity was as high as 71.4% in BC tissues and 33.6% in urine samples, which exhibited a significant correlation with both the grade and stage of cancer. 57 However, another meta-analysis from Iran indicated a lack of notable correlation between HPV infection and BC.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…27,57 A recent meta-analysis has demonstrated that HPV may be involved in the development and progression of BC, as well as contribute to the unfavorable prognosis of patients. 41 Moreover, a study in Iran revealed that HPV positivity was as high as 71.4% in BC tissues and 33.6% in urine samples, which exhibited a significant correlation with both the grade and stage of cancer. 57 However, another meta-analysis from Iran indicated a lack of notable correlation between HPV infection and BC.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, extensive evidence has demonstrated a strong correlation between HPV and BC, with the virus significantly affecting the development and prognosis of BC (Table 2). 40 In their study, Sun et al 41 reported that HPV infection was correlated with a significantly increased risk and a worse prognosis for BC. Moreover, HPV infection causes chronic inflammation, which induces the excessive release of reactive oxygen species (ROS) and reactive nitrogen species (RNS) from epithelial cells, leading to DNA damage.…”
Section: Hpv and Bcmentioning
confidence: 99%
See 2 more Smart Citations
“…Вместе с тем появились публикации, указывающие на влияние ВПЧ на течение РМП. Так, результаты опубликованного в 2022 г. метаанализа демонстрируют ухудшение прогноза течения РМП у ВПЧ-инфицированных пациентов [15], в другой публикации указана определенная этиологическая роль ВПЧ-инфицирования в развитии РМП [16]. В определенной степени сходное мнение высказывает другая группа исследователей [17].…”
Section: Introductionunclassified